A short-interval longitudinal study of associations between psychological distress and hippocampal grey matter in early adolescence - Amanda Boyes; Jacob M. Levenstein; Larisa T. McLoughlin; Christina Driver; Lia Mills; Jim Lagopoulos; Daniel F. Hermens (Brain Imaging and Behavior, 2024)
This study of Australian adolescents ( N = 88, 12-13-years-old) investigated the relationship between hippocampal grey matter volume (GMV) and self-reported psychological distress (K10) at four timepoints, across 12 months. Participants were divided into two groups; those who had K10 scores between 10 and 15 for all four timepoints were categorised as “low distress” (i.e., control group; n = 38), while participants who had K10 scores of 16 or higher at least once over the year were categorised as “moderate-high distress” ( n = 50). Associations were tested by GEE fitting of GMV and K10 measures at the same time point, and in the preceding and subsequent timepoints. Analyses revealed smaller preceding left GMV and larger preceding right GMV were associated with higher subsequent K10 scores in the “moderate-high distress” group. This was not observed in the control group. In contrast, the control group showed significant co-occurring associations (i.e., at the same TP) between GMV and K10 scores. The “moderate-high distress” group experienced greater variability in distress. These results suggest that GMV development in early adolescence is differently associated with psychological distress for those who experience “moderate-high distress” at some point over the year, compared to controls. These findings offer a novel way to utilise short-interval, multiple time-point longitudinal data to explore changes in volume and experience of psychological distress in early adolescents. The results suggest hippocampal volume in early adolescence may be linked to fluctuations in psychological distress.